2010
DOI: 10.1111/j.1746-1049.2010.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Diversity, Property Rights, and Natural Resources

Abstract: Countries rich in natural resources constitute both development failures and successes depending on their underlying socioeconomic fundamentals. Recent empirical evidence and theoretical work provide support for a resource-curse hypothesis based on ethnic fractionalization. There is also increasing empirical evidence suggesting that ethnic heterogeneity based on polarization is a strong deterrent of economic growth. In this paper, we explore the interlinkages between natural resource abundance and both measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 63 publications
(115 reference statements)
3
20
1
Order By: Relevance
“…risk level in investing in the resource) has little effect on individual investment and extraction levels; and (3) the action-reaction feedback is fundamental in determining the success or failure of communities, at least within the limits of our study. Our results confirm the basic dynamics of Ostrom's behavioral model of collective action (Ostrom 1998 Correlogram between variables Montalvo andReynal-Querol 2005, Baggio andPapyrakis 2010). Correcting for correlation between error terms (in the manner proposed by Zellner (1962)), increases the efficiency of the estimated coefficients and decreases our system's sensitivity to specification errors.…”
Section: Resultssupporting
confidence: 77%
“…risk level in investing in the resource) has little effect on individual investment and extraction levels; and (3) the action-reaction feedback is fundamental in determining the success or failure of communities, at least within the limits of our study. Our results confirm the basic dynamics of Ostrom's behavioral model of collective action (Ostrom 1998 Correlogram between variables Montalvo andReynal-Querol 2005, Baggio andPapyrakis 2010). Correcting for correlation between error terms (in the manner proposed by Zellner (1962)), increases the efficiency of the estimated coefficients and decreases our system's sensitivity to specification errors.…”
Section: Resultssupporting
confidence: 77%
“…Several papers suggest that mineral 9 resources hamper the development of a good institutional framework, e.g. by breeding corruption and rent-seeking (Baggio and Papyrakis, 2010;Bulte et al, 2005;Isham et al, 2005;Leite and Weidman, 2002;Torvik, 2002). Several papers have associated mineral resources with rent-seeking by focusing on the role of (mineral-rent distorted)…”
Section: Institutions (As Dependent Variable)mentioning
confidence: 99%
“…There have been several empirical cross-country analyses (using regression analysis) demonstrating a strong negative correlation between mineral resources and several institutional variables (e.g. for corruption, see Arezki and Brückner, 2011;Leite and Weidmann, 2002, for rule of law, see Kolstad, 2009;Norman, 2009;Sala-i-Martin and Subramanian, 2012; for quality of bureaucracy, see Brunnschweiler andBulte, 2008, Isham et al, 2005; for property rights protection see Baggio and Papyrakis, 2010;Brunnschweiler, 2008, for transparency see Williams, 2011).…”
Section: Institutions (As Dependent Variable)mentioning
confidence: 99%
“…Much of the so-called resource curse literature has developed theoretical and empirical research explaining the negative correlation observed between several measures of mineral abundance and long-term economic growth (Andersen and Aslaksen, 2008;Arezki and van der Ploeg, 2010;Baggio and Papyrakis, 2010;Caselli and Cunningham, 2009;Gylfason and Zoega, 2006;Kolstad, 2009;Murshed and Serino, 2011;Gerlagh, 2004, 2007;Papyrakis, 2011Papyrakis, , 2014Sachs and Warner 1995, 1997, 1999a, 1999b). Much of this literature (to which this paper belongs) pays particular attention to oil and its correlates (e.g.…”
Section: Introductionmentioning
confidence: 99%